2016
DOI: 10.1186/s12880-016-0143-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dosimetry of 18F-FDG PET/CT: incorporating exam-specific parameters in dose estimates

Abstract: BackgroundWhole body fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) is the standard of care in oncologic diagnosis and staging, and patient radiation dose must be well understood to balance exam benefits with the risk from radiation exposure. Although reference PET/CT patient doses are available, the potential for widely varying total dose prompts evaluation of clinic-specific patient dose. The aims of this study were to use exam-specific information to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 30 publications
(44 reference statements)
4
74
2
1
Order By: Relevance
“…Others demonstrated an increase in CT dose when moving from a standard protocol to a diagnostic protocol [22] or from low-dose protocols to contrast-enhanced protocols [23]. Willowson et al [8] showed that PET ED decreases from 6.3 to 6.0 mSv when ED is scaled to individual patient weight.…”
Section: Discussionmentioning
confidence: 99%
“…Others demonstrated an increase in CT dose when moving from a standard protocol to a diagnostic protocol [22] or from low-dose protocols to contrast-enhanced protocols [23]. Willowson et al [8] showed that PET ED decreases from 6.3 to 6.0 mSv when ED is scaled to individual patient weight.…”
Section: Discussionmentioning
confidence: 99%
“…A coefficient for calculating an effective dose is 1.26 μSv/MBq using the tissue‐weighting factor of the International Commission on Radiological Protection (International Commission on Radiological Protection (ICRP), ). So, the total effective dose was 1.0–1.9 mSv per single injection in compare, for example, with about 7–9 mSv from injected 18 F‐FDG activity 370–450 MBq (Marti‐Climent et al, ; Quin, Dauer, Pandit‐Taskar, Scholder, & Dauer, ).…”
Section: Methodsmentioning
confidence: 81%
“…In Table 4, we compared the radiation doses of 64 Cu-BaBaSar-RGD 2 with a few other PET probes including 18 F-galacto-RGD [9], 18 F-FDG [27], and 64 Cu-RGD 4 [28]. The absorbed doses in the heart, and brain were much lower for 64 Cu-BaBaSar-RGD 2 than those for 18 F-FDG.…”
Section: Discussionmentioning
confidence: 99%